Pseudo-Evaluative Behavior in Mathematical Problem Solving: An Analysis of Students’ Metacognitive Processes in Matrix Addition - Dediromario Wasahua; Surya Sari Faradiba (Mandalika Mathematics and Educations Journal, 2026)
Metacognitive regulation is widely acknowledged as a key component that supports students in managing their thinking during mathematical problem solving. This study investigates the metacognitive processes demonstrated by a student while completing matrix addition tasks, with a specific focus on the components of planning, monitoring, and evaluating. The research was conducted in a public senior high school in North Halmahera during November and December 2025. One eleventh grade student was purposively selected to provide an in-depth illustration of metacognitive regulation. A qualitative case study design was employed, and data was gathered through written work, direct observation, and semi structured interviews. Analysis was carried out using metacognitive process indicators to capture how the participant organized, controlled, and reviewed each stage of problem solving. The findings show that the participant performed planning effectively by identifying relevant information and determining an approach to the task, and monitoring was evident throughout the solution process. The evaluating phase appeared limited because the participant mainly checked the final answer without engaging in deeper reflection such as analyzing sources of error or comparing alternative procedures. This pattern is characterized in the study as pseudo evaluative behavior, indicating evaluation that is present yet incomplete. The study underscores the need for instructional practices that intentionally strengthen student’s evaluative metacognition during mathematical problem solving.